License to look? The role of permissive beliefs, desire thinking, and self-control in predicting the use of social networking sites. (April 2023) - Brandtner, Annika; Verduyn, Philippe; Behrens, Sofie; Spada, Marcantonio M.; Antons, Stephanie
Highlights: Desire thinking does not increase permissive beliefs in SNS users. Permissive beliefs are not associated with addictive SNS use. Permissive beliefs predict SNS use in daily life. Abstract: Permissive beliefs are considered the most proximal predictor of actual behavior. Whereas they have frequently been researched in substance-use disorders, the field of social networking sites (SNS) use is missing the investigation as to how relevant permissive beliefs might be in this context, what might be causal precursors of permissive beliefs (i.e., desire thinking), and which processes might influence the effect that permissive beliefs have on actual behavior (i.e., self-control). To answer these questions, 116 people who use SNS participated in an online survey that contained an experimental manipulation of desire thinking and questionnaires measuring permissive beliefs, self-control, and severity of problematic SNS use. In a one-week follow-up, 85 participants reported their SNS usage times. Results showed that the association between permissive beliefs and tendencies to use SNS problematically was not significant. The experimental manipulation led to a decrease in permissive beliefs in the control condition, but did not increase permissive beliefs in the desire thinking condition. Permissive beliefs predicted SNS use in the follow-up assessment, which was not moderated by self-control. The results suggest that permissive beliefs seem to be unrelated to addictive tendencies of SNS use, but are nevertheless associated with daily use. Desire thinking does not appear to activate permissive beliefs in this study, possibly because the use of social networks is less often experienced as conflicting. Due to its ubiquitous availability, the use of social networks itself might quickly resolve the conflict between desires and possible regulatory attempts, making good reasons for use unnecessary.